Evaluation of 'care bundles' for patients with chronic obstructive pulmonary disease (COPD): a multisite study in the UK. Issue 1 (30th May 2019) - Morton, Katherine; MacNeill, Stephanie; Sanderson, Emily; Dixon, Padraig; King, Anna; Jenkins, Sue; Metcalfe, Chris; Shaw, Ali; Chalder, Melanie; Benger, Jonathan; Hollingworth, William; Calvert, James; et al.
Abstract : Background: Chronic obstructive pulmonary disease (COPD) accounts for 10% of emergency hospital admissions in the UK annually. Nearly 33% of patients are readmitted within 28 days of discharge. We evaluated the effectiveness of implementing standardised packages of care called 'care bundles' on COPD readmission, emergency department (ED) attendance, mortality, costs and process of care. Methods: This is a mixed-methods, controlled before-and-after study with nested case studies. 31 acute hospitals in England and Wales which introduced COPD care bundles (implementation sites) or provided usual care (comparator sites) were recruited and provided monthly aggregate data. 14 sites provided additional individual patient data. Participants were adults admitted with an acute exacerbation of COPD. Results: There was no evidence that care bundles reduced 28-day COPD readmission rates: OR=1.02 (95% CI 0.83 to 1.26). However, the rate of ED attendance was reduced in implementation sites over and above that in comparator sites (implementation: IRR=0.63 (95% CI 0.56 to 0.71); comparator: IRR=1.12 (95% CI 1.02 to 1.24); group–time interaction p<0.001). At implementation sites, delivery of all bundle elements was higher but was only achieved in 2.2% (admissions bundle) and 7.6% (discharge bundle) of cases. There was no evidence of cost-effectiveness. Staff viewed bundles positively, believing they help standardise practice and facilitate communication between clinicians. However, they lacked skills in change management, leading to inconsistent implementation. Discussion: COPD care bundles were not effectively implemented in this study. They were associated with a reduced number of subsequent ED attendances, but not with change in readmissions, mortality or reduced costs. This is unsurprising given the low level of bundle uptake in implementation sites, and it remains to be determined if COPD care bundles affect patient care and outcomes when they are effectively implemented. Trial registration number: ISRCTN13022442 .